PERLAWANAN RAKYAT PALEMBANG TAHUN 1812 TERHADAP PEMERINTAH INGGRIS - Silalahi, Octaviandra Sialahi; Hutagaol, Elsa Hutagaol; Sitorus, Rutlilis Manogito; Sinaga, Rosmaida Sinaga (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
The aim of this research was to find out how the people of Palembang resisted the British government in 1812. This resistance resulted in the British reaction to control the Palembang Sultanate after the British gained the Dutch East Indies. The military journey led by the British met strong resistance from the Sultanate of Palembang which was supported by its people. The Musi River, with its harsh natural conditions, played an important role in this resistance. Fire rafts and logs were used by the Sultan of Palembang as a fortification to stop the British fleet.